Sunflower Waste Biomass as an Remarkable Adsorbent for Removal Heavy Metals from Aqueous Solution - Mohammadkhani 1, Shima; Yeganeh 2, Jaber; Nazemi 3*, Saeid (Shahroud Journal of Medical Sciences, 2016)
Background: Today, through various industrial processes, toxic heavy metals are released into aquatic environments that are harmful to the ecosystem. In the present investigation, removal of such contaminants from industrial wastewater is necessary. The purpose was made to extend an ecofriendly technology by using a bio carbon generated from sunflower waste biomass.Methods: The impact of initial pH of solution (2–10), initial heavy metal concentration, and bio carbon dose on the adsorption processes was studied. The residual concentration of samples, Cr(III), Cd(II) and Pb(II) after adding adsorbent and then filteration was determined using atomic absorption spectroscopy.Results: The equilibrium data were found to be well described by the Langmuire model. The Langmuire isotherm feasibility was checked with the dimensionless separation factor (RL).Conclusions: The introduction of a new adsorbent represents a great challenge for both academia and industry, and among all of the methods for removal contamination, we choose adsorption processes. Overall, the work demonstrates the possible use of sunflower waste biomass, as an effective adsorbent for the removal of heavy metals from wastewater.